Pharmacological TLR4 antagonism using topical resatorvid blocks solar UV-induced skin tumorigenesis in SKH-1 mice - Blohm-Mangone, Karen (Cancer Prev Res (Phila), 2018)
An urgent need exists for the development of more efficacious molecular strategies targeting non-melanoma skin cancer (NMSC), the most common malignancy worldwide. Inflammatory signaling downstream of Toll-like receptor 4 (TLR4) has been implicated in several forms of tumorigenesis, yet its role in solar UV-induced skin carcinogenesis remains undefined. We have previously shown in keratinocyte cell culture and SKH-1 mouse epidermis that topical application of the specific TLR4 antagonist resatorvid (TAK-242) blocks acute UV-induced AP-1 and NF-κB signaling, associated with downregulation of inflammatory mediators and MAP Kinase phosphorylation. We therefore explored TLR4 as a novel target for chemoprevention of UV-induced NMSC. We selected the clinical TLR4 antagonist resatorvid based upon target specificity, potency, and physico-chemical properties. Here we confirm using ex-vivo permeability assays that topical resatorvid can be effectively delivered to skin, and using in vivo studies that topical resatorvid can block UV-induced AP-1 activation in mouse epidermis. We also report that in a UV-induced skin tumorigenesis model, topical resatorvid displays potent photochemopreventive activity, significantly suppressing tumor area and multiplicity. Tumors harvested from resatorvid-treated mice display reduced activity of UV-associated signaling pathways and a corresponding increase in apoptosis compared to tumors from control animals. Further mechanistic insight on resatorvid-based photochemoprevention was obtained from unsupervised hierarchical clustering analysis of protein readouts via reverse-phase protein microarray revealing a significant attenuation of key UV-induced proteomic changes by resatorvid in chronically treated high-risk SKH-1 skin prior to tumorigenesis. Taken together, our data identify TLR4 as a novel molecular target for topical photochemoprevention of NMSC.